Analyzing the Impact of Financial Literacy and Credit Scoring on MSME’s Performance - Siska, Elmira; Purwatingningsih, Purwatingningsih; Hasanudin, Hasanudin; Ramadina, Haliza Nur; Marlina, Desi (Journal of Business and Economics Research (JBE), 2024)
MSMEs play an important role in the economy. However, many MSME actors experience obstacles in accessing formal financing. Low levels of financial literacy and lack of understanding of credit scores are often the main obstacles to the development of MSMEs. This study aims to analyze the effect of financial literacy and credit scoring on the performance of MSMEs in the city of Depok. The research design used is quantitative. Primary data was obtained from a questionnaire distributed to 99 respondents via Google from during August 2024. The criteria for respondents who could fill out the questionnaire were determined using a purposive sampling technique. Data processing was carried out using the Smart PLS 4 program which includes outer model analysis (convergent Validity, discriminant validity, reliability), inner model analysis (multicollinearity, R-square, goodness of fit, F-square, and path coefficients). This research concludes that financial literacy has a positive and significant effect on MSME's performance (t-statistic 3.278 > t table 1.96 and p value is 0.000 < 0.05), whereas the credit does not have a significant effect on MSME's performance (t-statistic 1.114 < t table 1.96 and p value is 0.089 > 0.05).